Crafting, Grounding, and Acceptability of a Local History as Embodiment of a Local Filipino Legend - Navas, Elena Abuan (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2025)
This research describes the process of collecting historical data and crafting it into a written form that aims to translate a local event from the past into a historical legend. The narrative complements the dearth of local Filipino literature that informs, entertains, and inculcates local culture and values. Despite the influx of local stories in towns and provinces around the Philippine archipelago, only old tales are repeatedly compiled, and published. This paper addresses this gap by documenting a local town history. There were two sources utilized in obtaining the historical data of the narrative: local history books of Alicia town and Isabela province in north Philippines including church pamphlets; and a semi-structured interview form. The high acceptability and grounding of the narrative are due to its closeness to the real event, revealing that respondents manifested a shared understanding of the meaning of the legend. This research recommends the need for more storytellers. Due to the limited time and resources, adjacent towns were not explored. The written narrative could have been widely-sourced and hence richer. The narrative’s effectiveness to inform and educate the young was not also explored. It is also recommended that this narrative be integrated to History and Character Education subjects in upper elementary or high schools, a true test of its effectiveness and a way to realize the rootedness of their culture or why they do what they do. The duty of the storyteller or researcher is to provide experiences making them realize the importance of local stories.